2020
DOI: 10.15517/rbt.v68is1.41201
|View full text |Cite
|
Sign up to set email alerts
|

Independent evolutionary lineage of the clingfish Gobiesox adustus (Gobiesocidae) from Isla del Coco, Costa Rica

Abstract: Introduction: Isla del Coco is an important protected area for marine fauna in the Eastern Tropical Pacific. In this area, the species that inhabit the intertidal zone have been subject to few studies. One of the species inhabiting these areas is the clingfish Gobiesox adustus (Gobiesocidae). Objective: To analyze for the first time the mitochondrial gene cytochrome oxidase subunit 1 (cox1) of G. adustus’ population from Isla del Coco and compare it with those of continental coast of Costa Rica and Ecuador. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
2
4
0
1
Order By: Relevance
“…To the best of our knowledge, our study is the first to assess the demographic history of a marine fish in the TEP using genome-wide nuclear DNA. Our results support previous findings of marine population expansions in the TEP occurring prior to the LGM [29][30][31][32]. This pattern is consistent with our analyses using both slow and fast mutation rates for H. passer, which showed population expansions beyond 30 Kya.…”
Section: Demographic History Of H Passersupporting
confidence: 93%
See 2 more Smart Citations
“…To the best of our knowledge, our study is the first to assess the demographic history of a marine fish in the TEP using genome-wide nuclear DNA. Our results support previous findings of marine population expansions in the TEP occurring prior to the LGM [29][30][31][32]. This pattern is consistent with our analyses using both slow and fast mutation rates for H. passer, which showed population expansions beyond 30 Kya.…”
Section: Demographic History Of H Passersupporting
confidence: 93%
“…However, only a few species have reported population expansions prior to the LGM [27]. On the contrary, in the TEP, most studies that have assessed the demographic history of marine organisms have found population expansions that precede the LGM [29][30][31][32] and few reporting population expansions in the last 20 Kya [32,33]. For instance, the goby, Elacatinus puncticulatus, and clingfish, Gobieosox adustus, experienced a population expansion around 170-130 Kya and 200-150 Kya, respectively [29,31].…”
Section: Demographic History Of H Passermentioning
confidence: 99%
See 1 more Smart Citation
“…Briggs & Bowen, 2012;Ekman, 1953;Hastings, 2000;Robertson & Cramer, 2009;), enfocados tanto en especies ícticas asociados a zonas intermareales como en aquellas asociados a zonas arrecifales en general, han demostrado repetidamente la importancia de barreras tales como las brechas arenosas de Sinaloa y Centroamericana, los giros oceánicos y patrones de corrientes marinas, incluyendo zonas de afloramientos costeros, entre otros, limitando o afectando la capacidad de dispersión (en estadios larvales y adultos) y colonización de nuevos ambientes de tales organismos, resultando así en una importante estructuración poblacional e incluso procesos de especiación a escala local. En ese mismo sentido, gran parte de las especies residentes en el intermareal rocoso y parte de aquellas transitorias asociadas a arrecifes rocosos/coralinos en el PTO, presentando además hábitos crípticos, muestran, por lo general, capacidades físicas de dispersión bastante limitadas, no solo en estadios tempranos [dada una corta duración del estadio larval y ornamentación reducida limitando así su arrastre/traslado por corrientes marinas, entre otras (Aceves-Medina et al, 2004;Beldade, Pedro, y Gonçalves, 2007;Taylor & Hellberg, 2005;Torres-Hernández et al, 2020)], sino también en estadios adultos [presentando una limitada capacidad de nado y asociaciones restrictas y bastante específicas con determinados tipos de sustratos o inclusive con otros organismos no móviles o de movilidad limitada (Piñeros et al, 2019;Sandoval-Huerta et al, 2019;Taylor & Hellberg, 2005; entre otros] propiciando o explicando, aunado a lo anterior, el nivel de estructuración, segregación y diferenciación taxonómica observado en el presente estudio. Como ejemplo, el efecto de las barreras arenosas de Sinaloa y Centroamericana (localizadas frente a las costas de Sinaloa, México y en el sur de México-El Salvador, respectivamente) es bastante evidente en el presente estudio separando gráficamente los conjuntos faunísticos del sur de Baja California Sur-Golfo de California, la costa centro-sur Mexicana y la costa centro sur de Centro América-Colombia, los cuales corresponden, respectivamente, con las definiciones de las provincias biogeográficas Cortez, Mexicana y Panámica, según Ekman (1953) y Hastings (2000.…”
Section: Discussionunclassified
“…On the contrary, in the TEP, most studies that have assessed the demographic history of marine organisms have found population expansions that precede the LGM [ 31 34 ] and few reporting population expansions in the last 20 Kya [ 34 , 35 ] . For instance, the goby, Elacatinus puncticulatus , and the clingfish, Gobieosox adustus , experienced a population expansion around 170–130 Kya and 200–150 Kya, respectively [ 31 , 33 ] . While another reef fish, Anisotremus interruptus , experienced an expansion in its continental populations after the LGM (∼5 kya).…”
Section: Main Contentmentioning
confidence: 99%